2021
DOI: 10.3390/ijms22115915
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Accelerates Bovine In Vitro-Produced Blastocyst Formation through the Hippo/YAP Pathway

Abstract: The segregation of trophectoderm (TE) and inner cell mass in early embryos is driven primarily by the transcription factor CDX2. The signals that trigger CDX2 activation are, however, less clear. In mouse embryos, the Hippo-YAP signaling pathway is important for the activation of CDX2 expression; it is less clear whether this relationship is conserved in other mammals. Lysophosphatidic acid (LPA) has been reported to increase YAP levels by inhibiting its degradation. In this study, we cultured bovine embryos i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Additionally, data derived from our time-lapse experiments show that within the same culture wells TE cysts expand faster in twin blastoids than in singleton blastoids (linear regression, P < 0.0001, Figure S1H, Supporting Information). Given that LPA has been reported to accelerate in vitro blastocyst formation in bovines [33] and we indeed see an increase in cyst diameter in response to increasing LPA concentrations (Kruskal-Wallis test, P < 0.0001, Figure S1I, Supporting Information), we suspected that accelerated TE expansion may drive the ICM splitting in our system. This is further supported by the finding that delaying TE induction by 24 h decreased twin blastoid formation (Student's t-test, P = 0.019, Figure S1J, Supporting Information).…”
Section: Te Expansion Drives Icm Divisionmentioning
confidence: 82%
“…Additionally, data derived from our time-lapse experiments show that within the same culture wells TE cysts expand faster in twin blastoids than in singleton blastoids (linear regression, P < 0.0001, Figure S1H, Supporting Information). Given that LPA has been reported to accelerate in vitro blastocyst formation in bovines [33] and we indeed see an increase in cyst diameter in response to increasing LPA concentrations (Kruskal-Wallis test, P < 0.0001, Figure S1I, Supporting Information), we suspected that accelerated TE expansion may drive the ICM splitting in our system. This is further supported by the finding that delaying TE induction by 24 h decreased twin blastoid formation (Student's t-test, P = 0.019, Figure S1J, Supporting Information).…”
Section: Te Expansion Drives Icm Divisionmentioning
confidence: 82%
“…Studies have reported that Hippo-YAP signaling is important for the activation of nuclear transcription factor CDX2 expression in mouse embryos [ 30 , 31 ]. Meanwhile, CDX2 is preferentially expressed in GC [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence was performed according to Yu et al [79] with some modifications. The embryos were fixed in 4% paraformaldehyde for 1 h at 4 • C. Subsequently, the embryos were permeated with 0.5% Triton X-100 (Sigma-Aldrich, St. Louis, MO, USA) at room temperature for 40 min.…”
Section: Immunofluorescence Staining Of Embryomentioning
confidence: 99%